Enhancement of lower limb motor imagery ability via dual-level multimodal stimulation and sparse spatial pattern decoding method - Hou, Yao; Gu, Zhenghui; Yu, Zhu Liang; Xie, Xiaofeng; Tang, Rongnian; Xu, Jinghan; Qi, Feifei (Frontiers in Human Neuroscience, 2022)
Recently, motor imagery brain-computer interfaces (MI-BCIs) with stimulation systems have been developed in the field of motor function assistance and rehabilitation engineering. An efficient stimulation paradigm and Electroencephalogram (EEG) decoding method have been suggested to enhance the performance of MI-BCI systems. Accordingly, in this study, a multimodal dual-level stimulation paradigm is designed for lower-limb rehabilitation training, whereby visual and auditory stimulations act on the sensory organ while proprioceptive and functional electrical stimulations are provided to the lower limb. In addition, upper triangle filter bank sparse spatial pattern (UTFB-SSP) is proposed to automatically select the optimal frequency sub-bands related to desynchronization rhythm during enhanced imaginary movement to improve the decoding performance. The effectiveness of the proposed MI-BCI system is demonstrated on an the in-house experimental dataset and the BCI competition IV IIa dataset, in comparison with other methods. Experimental results indicate that the proposed system can effectively enhance the MI performance by inducing the $ α $, $ β $ and $ γ $ rhythms in lower-limb movement imagery tasks.